Finding Resources to Reduce Class-size - Odden, Allan; Archibald, Sarah (Education Policy Analysis Archives, 2001)
This article discusses how a medium-sized school district in Wisconsin was able to reallocate resources to reduce class sizes in grades K-5 without spending more money or increasing its tax rate. Previous research on resource reallocation found that the bulk of reallocated resources were those supporting categorical program services. This district was able to use a different strategy. As a growing district, its marginal costs of adding an extra class of students were much less than its average expenditures per pupil, which were reimbursed by the state school finance formula. As the district grew, therefore, it acquired excess revenues. Also, by implementing full-day kindergarten, the district acquired more excess revenues because this added (0.5 pupil) X (Number of kindergartners) to its current enrollment, and the cost of educating these students was less than the amount they received from the state funding formula. It then used these revenues to reduce class sizes to between 15 and 20 in all Kindergarten through grade 3 classrooms and to between 15 and 22 for grades 4-5.